A femtosecond laser-based hydrogel-based Janus porous film processing method
Through femtosecond laser processing technology, combined with PDMS and hydrogel materials, a hydrogel-based Janus porous film with superior biocompatibility and versatility was prepared, which solved the problems of single material, complex preparation and single function in the prior art, and achieved widespread application in the field of biomedical.
Patent Information
- Application Number
- CN202310366900.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-07
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2043-04-07
AI Technical Summary
The application of existing Janus porous films in the field of biomedical science is limited by the problems of single materials, complex preparation technology and single functions, and lack of biomimetic porous films with good biocompatible properties.
Using the hydrogel-based Janus porous film processing method based on femtosecond laser, Janus films with different sizes of conical micropores were prepared by preparing PDMS prepolymer solution and hydrogel prepolymer solution, and using femtosecond laser processing technology.
The high biocompatibility, simplified preparation process and versatility of Janus porous films have been achieved, making it of important application value in biomedical, drug delivery, substance separation and microfluidics.
Smart Images

Figure CN116376104B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of micro-nano manufacturing, and in particular to a femtosecond laser-based hydrogel-based Janus porous film processing method. Background Art
[0002] Janus film means that the morphology or chemical composition on both sides of the same film has two different properties. There are a large number of microscale Janus porous film structures in nature, such as lotus leaf structure with super wettability, cactus thorn with unidirectional transport characteristics and cell membrane with intelligent gating characteristics. Since Janus structure has the advantages of self-cleaning, anti-icing and anti-pollution, it has important application value in the fields of energy, environment, microfluidics and biomedicine.
[0003] In recent years, with the development of advanced manufacturing technology, Janus porous films have been prepared more and more conveniently. Among them, femtosecond laser processing technology is an ideal means of preparing porous films in the biomedical field because of its advantages of true three-dimensionality, small heat-affected zone, no mask and no pollution. For example, in 2018, the research group of Professor Duan Jian of Central South University used femtosecond laser direct writing technology to prepare micro-nano structure arrays on copper foam. The copper foam exhibited Janus super-wetting properties with one side hydrophilic and the other side hydrophobic, and had good water mist collection capabilities, but the materials used in the above method were single and not biocompatible. In 2019, the research group of Professor Wu Dong of the University of Science and Technology of China used femtosecond laser ablation combined with nanoparticle deposition technology to prepare Janus porous films. This preparation technology is relatively complex and the film thickness is difficult to accurately control.
[0004] At present, Janus membranes are still in the exploratory stage in the biomedical field. The functions of porous membranes are relatively simple and the preparation technology is relatively complex. Therefore, the development of biomimetic porous membranes with good biocompatibility and simple preparation process is of great significance in biomedical fields such as bleeding control, wound healing and drug delivery. Summary of the invention
[0005] In order to make up for the deficiencies of the prior art, the present invention provides a femtosecond laser-based hydrogel-based Janus porous film processing method with high precision, high production efficiency and good product performance.
[0006] The present invention is achieved through the following technical solutions:
[0007] A femtosecond laser-based hydrogel-based Janus porous film processing method comprises the following steps:
[0008] (1) Prepare PDMS prepolymer solution and prepare PDMS film: mix polydimethylsiloxane (PDMS) solution with crosslinking agent, stir, evacuate, use a coating machine to spin coat, and then heat and cure to obtain a PDMS film with uniform thickness;
[0009] (2) Femtosecond laser processing of PDMS micro-through holes: The galvanometer device in the femtosecond laser processing system is used to focus the laser beam onto the surface of the PDMS film, and a line scanning path is adopted to select laser processing parameters to achieve the preparation of micro-through holes;
[0010] (3) preparing a hydrogel prepolymer solution and curing the hydrogel solution in the PDMS micropores: mixing acrylic acid (AAC), polyvinyl pyrrolidone (PVP), analytically pure pentaerythritol triacrylate (PETA), triethanolamine (TEA) and 4,4'-di(diethylamino)benzophenone (EMK), heating and stirring until completely dissolved to obtain a hydrogel prepolymer solution, pouring the hydrogel prepolymer solution into the prepared micro-through holes, and irradiating with ultraviolet light to obtain a cross-linked solid hydrogel-based film;
[0011] (4) Femtosecond laser in situ processing of hydrogel micro-through holes: Femtosecond laser is used to process PDMS micro-holes in situ to obtain Janus films with conical micro-hole arrays of different sizes.
[0012] The present invention utilizes the polydimethylsiloxane (PDMS) film spin coating technology and the bioaffinity characteristics of hydrogel to realize the preparation of hydrogel-based Janus films of different thicknesses; utilizes femtosecond laser in-situ etching technology to realize the one-step molding preparation of tapered through holes; and realizes flexible control of the tapered hole size by adjusting parameters such as laser scanning speed, scanning spacing and scanning times.
[0013] The hydrogel-based Janus porous film prepared by the present invention has good biocompatibility. By combining the hydrophobicity of PDMS and the hydrophilicity of the hydrogel, the Janus film has excellent asymmetric wetting properties. In addition, the preparation of micro-through holes of different sizes can be achieved by accurately controlling the thickness of the film and laser scanning parameters.
[0014] A better technical solution of the present invention is:
[0015] In step (1), the polydimethylsiloxane solution and the cross-linking agent are mixed in a mass ratio of 10:1.
[0016] A further preferred solution is that the spin coating speed of the coating machine is 100-1500r / min, and a PDMS film with a thickness of 100-500μm is obtained, wherein the prepolymer solution can be naturally allowed to stand and flow to obtain a 500μm thick PDMS film, and the spin-coated prepolymer solution PDMS film is placed in an oven for heating and curing to obtain a solid PDMS film.
[0017] In step (2), the laser processing parameters are scanning power 200-400 mW, scanning speed 1-6.5 mm / s, scanning times 1-5 times, and scanning spacing 5-60 μm; further preferred processing parameters are scanning power 300 mW, scanning speed 3 mm / s, scanning times 4 times, and scanning spacing 15 μm.
[0018] In step (3), 1 mL of acrylic acid and 0.2 g of polyvinyl pyrrolidone are uniformly mixed and ultrasonicated for 30 min, and then 0.1 mL of analytically pure pentaerythritol triacrylate, 0.7 mL of triethanolamine and 0.1 mL of 4,4'-di(diethylamino)benzophenone are added, and the mixed solution is heated to 50°C in a water bath and ultrasonicated for 1 h to obtain a hydrogel prepolymer solution.
[0019] In step (3), the hydrogel prepolymer solution is poured into the prepared micro-through-holes, which are then placed in a vacuum pump for evacuation, and then irradiated under ultraviolet light for 10 minutes.
[0020] In step (4), the hydrogel-based film is placed on a 3D mobile platform and processed according to a pre-designed PDMS micropore scanning path, with a scanning power of 200-400 mW, a scanning speed of 1-6.5 mm / s, a scanning number of 1-5 times, and a scanning spacing of 5-60 μm; further preferred processing parameters are: scanning power of 300 mW, scanning speed of 4 mm / s, scanning number of 3 times, and scanning spacing of 30 μm.
[0021] In step (4), the laser beam focusing spot is adjusted so that it is located on the surface of the hydrogel film, and the PDMS micropores are processed in situ to obtain conical through holes, wherein the diameter of the hole on one side of the PDMS is 200 μm, and the diameter of the hole on one side of the hydrogel is 250-300 μm.
[0022] The Janus film prepared by combining PDMS and hydrogel in the present invention has good elasticity, flexibility, water absorption and biocompatibility, wherein one side of the PDMS is hydrophobic and can be used for the transportation of biological fluids; the other side of the hydrogel is hydrophilic and can be used for the absorption of biological fluids; by adjusting the parameters of femtosecond laser scanning, the preparation of tapered through holes of different sizes can be achieved, the preparation method has simple process, high precision and high efficiency, and the thickness of the film and the size of the micropores can be flexibly controlled.
[0023] The present invention is the first to use PDMS combined with hydrogel as a base material to prepare a Janus porous film structure, and the film has important application value in the fields of biomedicine, drug delivery, material separation and microfluidics. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The present invention will be further described below in conjunction with the accompanying drawings.
[0025] Figure 1 Schematic diagram of spin coating of the PDMS film of the present invention;
[0026] Figure 2 Schematic diagram of the relationship between PDMS film thickness and the rotation speed of the coating machine;
[0027] Figure 3 It is a schematic diagram of the process flow of the present invention;
[0028] Figure 4 The scanning electron microscope images are of the PDMS film and the hydrogel porous film prepared in the present invention. DETAILED DESCRIPTION
[0029] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The drawings provide specific implementation examples of the present invention. However, the present invention can be implemented in many different forms and is not limited to the implementation examples described herein. Therefore, the purpose of providing this example is to make the disclosure of the present invention easier to understand.
[0030] Embodiment 1: A femtosecond laser-based hydrogel-based Janus porous film processing method comprises the following steps:
[0031] 1. Preparation of PDMS solution
[0032] 1.1 Mix liquid PDMS and crosslinker (Sylgard 184, Dow Corning) in a mass ratio of 10:1;
[0033] 1.2 Use a glass rod to stir for 10 minutes to mix the solution thoroughly;
[0034] 1.3 Vacuum the stirred PDMS solution and observe the bubbles in the PDMS solution. When the bubbles disappear completely, the prepared PDMS solution is obtained.
[0035] 2. Preparation of PDMS film
[0036] 2.1 Use a pipette to take an appropriate amount of the prepared PDMS solution and place it on the coverslip;
[0037] 2.2 Use a glue machine to spin coat. The thickness of the PDMS film (100μm-500μm) can be flexibly adjusted by changing the speed of the glue machine. Here, a speed of 200r / min is selected for spin coating, and finally a 400μm thick PDMS film is obtained;
[0038] 2.3 Place the spin-coated PDMS film in a 60°C oven and heat for 3 hours. Once it is completely cured, it can be used for femtosecond laser processing.
[0039] 3. Processing of PDMS conical micropores
[0040] 3.1 Use a titanium sapphire femtosecond laser (Elite-1K-HE, Coherence, pulse width 104fs, repetition rate 1KHz, center wavelength 800nm) to place the cured PDMS film on the 3D mobile platform;
[0041] 3.2 Import the designed line scan path in the path loading area;
[0042] 3.3 Laser scanning processing is performed by controlling the variable method. The greater the laser scanning power, the larger the hole diameter. When the power is too large, the actual hole diameter is larger than the preset diameter. When the power is too small, the through hole cannot be formed. Therefore, the scanning power selected here is 300mW. In addition, when other scanning parameters remain unchanged, the slower the scanning speed / the more scanning times / the smaller the scanning spacing, the larger the size of the micro through hole;
[0043] 3.4 According to the thickness of the PDMS film, select the corresponding scanning speed, scanning times and scanning spacing to prepare the tapered through hole (as shown in the following table):
[0044] ;
[0045] 3.5 The laser beam focusing spot is adjusted so that it is located on the surface of the PDMS film. During the processing, the Gaussian beam utilizes the micropore side wall reflection and plasma absorption to increase the micropore depth; with the increase of the laser beam repetition frequency, the micropore outlet diameter increases; with the increase of the micropore depth, the slag in the hole will disturb the laser beam, and the micropore entrance diameter will decrease, thereby realizing the preparation of conical micropores.
[0046] 4. Preparation of hydrogel solution
[0047] 4.1 Evenly mix 1 mL of AAC and 0.2 g of PVP and sonicate for 30 min;
[0048] 4.2 Add 0.1 mL of PETA, 0.7 mL of TEA and 0.1 mL of EMK to the above mixed solution;
[0049] 4.3 Heat the mixed solution to 50℃ in a water bath and ultrasonicate for 1h.
[0050] 5. Preparation of hydrogel solid film
[0051] 5.1 Use a pipette to drop the prepared hydrogel solution into the PDMS microwell array;
[0052] 5.2 Place it in a vacuum pump to evacuate and remove the air at the interface between PDMS and hydrogel;
[0053] 5.3 UVP high-intensity B-100 series lamp 21, 500 mW cm -2 ) for 10 min to obtain a hydrogel solid film.
[0054] 6. Processing of hydrogel conical micropores
[0055] 6.1 Place the cured hydrogel-based film on the 3D mobile platform;
[0056] 6.2 Processing according to the pre-designed PDMS micropore scanning path;
[0057] 6.3 Set the processing parameters: scanning power is 300mW, scanning speed is 4mm / s, scanning times is 3 times, and scanning interval is 30μm;
[0058] 6.4 Adjust the laser beam focus spot so that it is located on the surface of the hydrogel solid film, and process the PDMS micropores in situ to obtain conical through holes, where the diameter of the hole on the PDMS side is 200 μm and the diameter of the hole on the hydrogel side is 300 μm (see attached). Figure 4 ).
[0059] The prepared Janus film was taken for contact angle test. The contact angle on the PDMS side was 158.5°, which was hydrophobic; the contact angle on the hydrogel side was 14.3°, which was hydrophilic. The above results show that the Janus porous film has obvious asymmetric wetting characteristics.
[0060] Embodiment 2: A femtosecond laser-based hydrogel-based Janus porous film processing method comprises the following steps:
[0061] 1. Preparation of PDMS solution
[0062] 1.1 Mix liquid PDMS and crosslinker (Sylgard 184, Dow Corning) in a mass ratio of 10:1;
[0063] 1.2 Use a glass rod to stir for 10 minutes to mix the solution thoroughly;
[0064] 1.3 Vacuum the stirred PDMS solution and observe the bubbles in the PDMS solution. When the bubbles disappear completely, the prepared PDMS solution is obtained.
[0065] 2. Preparation of PDMS film
[0066] 2.1 Use a pipette to take an appropriate amount of the prepared PDMS solution and place it on the coverslip;
[0067] 2.2 Use a spin coater to spin coat, here choose a speed of 400r / min to spin coat, and finally get a 300μm thick PDMS film;
[0068] 2.3 Place the spin-coated PDMS film in a 60°C oven and heat for 3 hours. Once it is completely cured, it can be used for femtosecond laser processing.
[0069] 3. Processing of PDMS conical micropores
[0070] 3.1 Use a titanium sapphire femtosecond laser (Elite-1K-HE, Coherence, pulse width 104fs, repetition rate 1KHz, center wavelength 800nm) to place the cured PDMS film on the 3D mobile platform;
[0071] 3.2 Import the designed line scan path in the path loading area;
[0072] 3.3 Laser scanning processing is carried out by controlling the variable method. The selected scanning power is 300mW, the scanning speed is 4mm / s, the scanning times is 3 times, and the scanning interval is 30μm.
[0073] 3.4 The laser beam focusing spot is adjusted so that it is located on the surface of the PDMS film. During the processing, the Gaussian beam utilizes the micropore side wall reflection and plasma absorption to increase the micropore depth; with the increase of the laser beam repetition frequency, the micropore outlet diameter increases; with the increase of the micropore depth, the slag in the hole will disturb the laser beam, and the micropore entrance diameter will decrease, thereby realizing the preparation of conical micropores.
[0074] 4. Preparation of hydrogel solution
[0075] 4.1 Evenly mix 1 mL of AAC and 0.2 g of PVP and sonicate for 30 min;
[0076] 4.2 Add 0.1 mL of PETA, 0.7 mL of TEA and 0.1 mL of EMK to the above mixed solution;
[0077] 4.3 Heat the mixed solution to 50℃ in a water bath and ultrasonicate for 1h.
[0078] 5. Preparation of hydrogel solid film
[0079] 5.1 Use a pipette to drop the prepared hydrogel solution into the PDMS microwell array;
[0080] 5.2 Place it in a vacuum pump to evacuate and remove the air at the interface between PDMS and hydrogel;
[0081] 5.3 UVP high-intensity B-100 series lamp 21, 500 mW cm -2 ) for 10 min to obtain a hydrogel solid film.
[0082] 6. Processing of hydrogel conical micropores
[0083] 6.1 Place the cured hydrogel-based film on the 3D mobile platform;
[0084] 6.2 Processing according to the pre-designed PDMS micropore scanning path;
[0085] 6.3 Set the processing parameters: scanning power is 300mW, scanning speed is 5mm / s, scanning times is 2 times, and scanning interval is 45μm;
[0086] 6.4 Adjust the laser beam focus spot so that it is located on the surface of the hydrogel solid film, and process the PDMS micropores in situ to obtain conical through holes, where the diameter of the hole on the PDMS side is 200 μm and the diameter of the hole on the hydrogel side is 250 μm.
[0087] The prepared Janus film was tested for contact angle. The contact angle on the PDMS side was 161°, which was hydrophobic; the contact angle on the hydrogel side was 14.4°, which was hydrophilic. The above results show that the Janus porous film still has obvious asymmetric wetting properties.
[0088] The invention realizes the preparation of a hydrogel-based Janus cone-shaped porous film structure by laser in-situ etching, and the film has excellent asymmetric wetting properties.
[0089] In the above embodiments, the best mode of implementation of the present invention has been described. Obviously, many changes can be made under the inventive concept of the present invention. It should be noted that any changes made under the inventive concept of the present invention will fall within the protection scope of the present invention.
Claims
1. A femtosecond laser-based hydrogel-based Janus porous film processing method, characterized in that: The steps include: (1) Mixing the polydimethylsiloxane solution and the cross-linking agent, stirring, and evacuating, and using a coating machine for spin coating at a coating speed of 100-1500 r / min to obtain a PDMS film with a thickness of 100-500 μm, and placing the spin-coated prepolymer solution PDMS film in an oven for heating and curing to obtain a solid PDMS film; (2) Using the galvanometer device in the femtosecond laser processing system to focus the laser beam onto the surface of the PDMS film, a line scanning path is adopted, and laser processing parameters are selected to achieve the preparation of micro-through holes; The laser processing parameters are: scanning power 200-400 mW, scanning speed 1-6.5 mm / s, scanning times 1-5 times, scanning spacing 5-60 μm; (3) mixing acrylic acid, polyvinyl pyrrolidone, analytically pure pentaerythritol triacrylate, triethanolamine and 4,4'-di(diethylamino)benzophenone, heating and stirring until completely dissolved to obtain a hydrogel prepolymer solution, pouring the hydrogel prepolymer solution into the prepared micro-through holes, and irradiating with ultraviolet light to obtain a cross-linked solid hydrogel-based film; (4) Placing the hydrogel-based film on a 3D mobile platform and processing it according to the pre-designed PDMS micropore scanning path. The processing parameters are: scanning power 200-400 mW, scanning speed 1-6.5 mm / s, scanning times 1-5 times, and scanning spacing 5-60 μm; Janus films with tapered micropore arrays of different sizes were obtained.
2. The processing method according to claim 1, characterized in that: In step (1), the polydimethylsiloxane solution and the cross-linking agent are mixed in a mass ratio of 10:
1.
3. The processing method according to claim 1, characterized in that: In step (3), 1 mL of acrylic acid and 0.2 g of polyvinyl pyrrolidone are uniformly mixed and ultrasonicated for 30 min, and then 0.1 mL of analytically pure pentaerythritol triacrylate, 0.7 mL of triethanolamine and 0.1 mL of 4,4'-di(diethylamino)benzophenone are added, and the mixed solution is heated to 50°C in a water bath and ultrasonicated for 1 h to obtain a hydrogel prepolymer solution.
4. The processing method according to claim 1 or 3, characterized in that: In step (3), the hydrogel prepolymer solution is poured into the prepared micro-through-holes, which are then placed in a vacuum pump for evacuation and then irradiated under ultraviolet light for 10 minutes.
5. The processing method according to claim 1, characterized in that: In step (4), the laser beam focusing spot is adjusted so that it is located on the surface of the hydrogel film, and the PDMS micropores are processed in situ to obtain conical through holes, wherein the diameter of the hole on one side of the PDMS is 200 μm, and the diameter of the hole on one side of the hydrogel is 250-300 μm.
6. The processing method according to claim 1, characterized in that: In step (2), the laser processing parameters are: scanning power 300 mW, scanning speed 3 mm / s, scanning times 4 times, and scanning spacing 15 μm.
7. The processing method according to claim 1, characterized in that: In step (4), the processing parameters are: scanning power 300 mW, scanning speed 4 mm / s, scanning times 3 times, and scanning interval 30 μm.